2019
DOI: 10.1556/004.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of tick-borne protozoan pathogens, Babesia sp. and Hepatozoon canis, in red foxes (vulpes vulpes) in Serbia

Abstract: Tick-borne haematozoans cause severe diseases in domestic animals, and some of them have zoonotic potential. The results of previous studies in Europe point to the important role of foxes in natural endemic cycles of several tick-borne pathogens, including protozoa. The aim of the present research was to acquire information on the prevalence and distribution of tick-borne protozoan parasites among foxes in Serbia. Legally hunted foxes from 14 localities throughout Serbia were analysed. Spleen samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Babesia canis was confirmed by PCR and sequencing in 4.2% (9/216) of golden jackals [ 66 ]. In red foxes, two Babesia species were identified by molecular methods: B. vulpes (28.7%) and B. canis in a single fox (0.8%) [ 67 ]. Co-infection with B. vulpes and H. canis was present in 20.2% of foxes.…”
Section: South-eastern Europementioning
confidence: 99%
“…Babesia canis was confirmed by PCR and sequencing in 4.2% (9/216) of golden jackals [ 66 ]. In red foxes, two Babesia species were identified by molecular methods: B. vulpes (28.7%) and B. canis in a single fox (0.8%) [ 67 ]. Co-infection with B. vulpes and H. canis was present in 20.2% of foxes.…”
Section: South-eastern Europementioning
confidence: 99%
“…Recent research has shown a high prevalence of H. canis in red foxes in Serbia, while no data are available for the other canids that are present [ 17 ]. Together with the golden jackal and red fox, the grey wolf is one of the three autochthonous species of wild carnivores in Serbia.…”
Section: Introductionmentioning
confidence: 99%
“…In Serbia, the occurrence of H. canis has been previously described in epidemiological surveys conducted on dogs [ 43 ], red foxes [ 44 ] and I. ricinus [ 19 ]. This study reports the presence of H. canis in R. sanguineus for the first time in the country.…”
Section: Discussionmentioning
confidence: 99%